The Need for a Unified Patent Court - Eugénio Lucas (LeXonomica, 2020)
This article discusses the need of a Unified Patent Court, as a major contribution for the implementation of the European unitary patent. It begins by outlining the evolution of European patent rights and identifying the problems of the current system. Implementing a Unified Patent Court will be defended as a solution for one of the most important problems of the European patent: the lack of a central mechanism of jurisdictional control. The current model of jurisdictional control gives rise to a situation of great legal uncertainty and has diminished the value of European Union patent rights. We will analyse the virtues and disadvantages of the new European Unitary Patent resulting from the adoption of Regulations (EU) 1257/2012 and 1260/2012 and the Agreement on a Unified Patent Court.